2015
DOI: 10.1007/s10517-015-2859-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on Biological Activity of Permafrost Microorganisms

Abstract: The number and viability of microorganism specimens Bacillus spp. isolated from permafrost soil remained unchanged after incubation at temperatures of -16-37°C. Experiments on F1 CBA/Black-6 mice showed that incubation of bacteria at -5°C for 72 h promotes a decrease in their toxicity and an increase in their immunostimulating effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The obtained data together with the previously obtained results [6,7,8,10] are the basis for raising a number of questions about the action mechanisms of metabolites of microorganisms from Permafrost on human immunocompetent cells. Considering also that TNFα, IL-1β and IL-10 are systemic cytokines that are responsible not only for the activation of the immune system, but also for the mobilization of regulatory systems such as the nervous and endocrine [3,14,15], it is possible to consider the possibility to use secondary metabolites of Permafrost microorganisms as a substrate for the development of new immunomodulators and adaptogens.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The obtained data together with the previously obtained results [6,7,8,10] are the basis for raising a number of questions about the action mechanisms of metabolites of microorganisms from Permafrost on human immunocompetent cells. Considering also that TNFα, IL-1β and IL-10 are systemic cytokines that are responsible not only for the activation of the immune system, but also for the mobilization of regulatory systems such as the nervous and endocrine [3,14,15], it is possible to consider the possibility to use secondary metabolites of Permafrost microorganisms as a substrate for the development of new immunomodulators and adaptogens.…”
Section: Resultssupporting
confidence: 52%
“…An experimental study of microorganisms (MO) of strain M3 Bacillus sp. isolated from permafrost of the late Neogene showed that a change in the temperature conditions of cultivation has a significant effect on the biological properties of bacteria in vitro and in vivo, in particular, it changes their enzymatic, immunotropic and reparative activity [6,7,8,10]. It seems relevant to study the effect of MB of MO from Permafrost on the functional activity of immunocompetent human cells in vitro for development, in the future, immunotropic drugs based on them.…”
Section: Introductionmentioning
confidence: 99%